Outdoor regenerative water purification and drinking water station based on semiconductor condensation technology - Gao, DengChang (International Journal of Scientific Research and Management (IJSRM), 2024)
In some exhibition sites and outdoor sports venues, there is still a lack of public drinking water resources and hand washing facilities., This topic in view of the existing problems put forward a new scheme, and designed a based on semiconductor condensation technology of outdoor regeneration net drink integration intelligent water station, photovoltaic energy storage technology and air water, realize the self-sufficiency of energy and water, and break the equipment in the regional limitations, make it to meet the needs of people hand clean and healthy drinking water, solve the problem of lack of clean water in specific places. In addition, the device integrates the neural network deep learning algorithm to predict the water consumption, and provides emergency charging and advertising and other functions, which has good social benefits and market prospects.